The Christian Genealogy of the New Culture Movement's “Anti-Superstition” Narrative - YANG, Jialun (Journal of Research for Christianity in China (JRCC), 2026)
The anti-superstition narrative of the New Culture Movement was not a secular construct that emerged out of thin air during the May Fourth period. In terms of its intellectual origins, this discourse of enlightenment internalized and appropriated the very object it originally intended to critique: the historical legacy of Christianity. From the late Qing period onward, missionary organizations, represented by the Christian Literature Society for China, pioneered a path of disenchantment by using natural science to critique local religious beliefs, based on the concept of natural theology. Subsequently, in establishing the authority of modern science, intellectuals of the New Culture Movement adopted the discursive framework of "using science to dispel superstition." However, by stripping "Ge Zhi Xue" of its natural theological connotations and reshaping it into "Mr. Science"—the embodiment of the standard of truth—the authority of modern science was thereby established. Beyond this relay of narrative structures, in the actual construction of their critiques, these intellectuals used cited field data collected by missionaries and adopted the classification criteria for "superstition" originally compiled by church scholars. During the height of the Anti-Christian Movement—indigenous Christian elites, in response to the ensuing social pressures, actively embraced the anti-superstition narrative established by the New Culture Movement. This discursive relay—which transcended the boundaries between religious denominations and the secular sphere—demonstrates that the power boundaries delineating "science," "religion," and "superstition" in modern China were dynamically generated through a complex interplay of intellectual borrowing, discursive displacement, and the tensions of the era.
Keywords: New Culture Movement, Anti-Superstition, Christianity